2010
DOI: 10.1002/ieam.77
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk assessment for the serotonin re‐uptake inhibitor fluoxetine: Case study using the European risk assessment framework

Abstract: The serotonin re-uptake inhibitor fluoxetine was selected for an environmental risk assessment, using the most recent European guideline (EMEA 2006) within the European Union (EU)-funded Environmental Risk Assessment of Pharmaceuticals (ERAPharm) project due to its environmental persistence, acute toxicity to nontarget organisms, and unique pharmacokinetics associated with a readily ionizable compound. As a widely prescribed psychotropic drug, fluoxetine is frequently detected in surface waters adjacent to urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 66 publications
(101 reference statements)
2
50
0
1
Order By: Relevance
“…Using current methods, environmental risk assessments for medicines that are ionized at environmental pH values are problematic in that they assume soil sorption characteristics (i.e., K OC , K OW ) that are not realistic and that will lead to predicting environmental fate incorrectly. A case study with the serotonin reuptake inhibitor fluoxetine concluded that new methods to predict the fate of ionisable compounds in soils are needed, as well as further research concerning factors determining environmental exposure to these compounds [32]. The present study establishes under controlled laboratory conditions kinetics and pathways of dissipation of these psychiatric drugs and that the products of soil amitriptyline transformation are bioactive.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Using current methods, environmental risk assessments for medicines that are ionized at environmental pH values are problematic in that they assume soil sorption characteristics (i.e., K OC , K OW ) that are not realistic and that will lead to predicting environmental fate incorrectly. A case study with the serotonin reuptake inhibitor fluoxetine concluded that new methods to predict the fate of ionisable compounds in soils are needed, as well as further research concerning factors determining environmental exposure to these compounds [32]. The present study establishes under controlled laboratory conditions kinetics and pathways of dissipation of these psychiatric drugs and that the products of soil amitriptyline transformation are bioactive.…”
Section: Discussionmentioning
confidence: 69%
“…Chem. 32,2013From Figures 2 and 3, we see significant differences exist in the dissipation kinetics of amitriptyline in the three different agriculture soils. The dissipation of amitriptyline in loam soil is much faster than that in clay and sandy soil.…”
Section: Extended Persistence Of Amitriptyline and Nortriptyline In Amentioning
confidence: 83%
See 1 more Smart Citation
“…Recently, Thomas focused his activities on the outcome of the ERAPharm project [19][20][21][22][23]. Thomas Knacker dedicated most of his professional life to the science of ecotoxicology.…”
Section: Dr Jörg Römbke Dr Anja Coorsmentioning
confidence: 99%
“…A considerable amount of work within the project focused on 3 case studies; 2 focused on human pharmaceuticals, the b-blocker atenolol (Kü ster et al 2010) and the antidepressant fluoxetine (Oakes et al 2010), and the third on a veterinary parasiticide, ivermectin (Liebig et al 2010). For these 3 compounds, environmental risk assessments were performed to evaluate and highlight the strengths and weaknesses of the existing European guidelines on environmental risk assessment of pharmaceuticals.…”
Section: Key Findingsmentioning
confidence: 99%